Pelatihan Pengucapan Bahasa Inggris melalui Pendengaran Ekstensif untuk Anak Anak di Panti Asuhan Putera Bonang Banjarmasin - Fitra Ramadani; Radityo Tri Nugroho; Kartini Kartini; Reza Pratama; M. Khairani (Pusat Riset dan Inovasi Nasional, 2025)
This community service program aimed to improve English pronunciation skills through an extensive listening method for children at Panti Asuhan Putera Bonang Banjarmasin. The research objectives were to investigate how effective the implementation of pronunciation training through extensive listening was and to assess the extent of its impact on the children's English pronunciation abilities. The methodology involved a combination of lectures, discussions, and structured exercises, including pretests and posttests. The program was conducted with 15 participants aged 12 to 15 years, most of whom had limited English proficiency. The results indicated significant improvement in the children's pronunciation skills, with average pretest scores rising from 62.93 to 81.33 in the posttest, accompanied by a decrease in standard deviation and error margin, suggesting a more consistent outcome. These findings highlight the effectiveness of the extensive listening method in enhancing pronunciation and fostering a more natural and enjoyable learning process for underprivileged children. The study suggests that similar interventions could be replicated in other orphanages to bridge the language gap and improve communication skills for future opportunities.